Renal function and anemia status determination at the early stages of kidney transplant function - Mozul, Sławomir; Załuska, Alicja; Książek, Piotr; Rudzki, Sławomir; Załuska, Wojciech (Polish Journal of Public Health, 2009)
Introduction. Along with the world tendency of increased number of patients with chronic kidney diseases, the number of individuals undergoing renal replacement therapy also augments. From all methods of such kind of therapy, renal transplantation is considered to be most optimal. The aim of this study was to assess the renal function during a 26-week follow-up post-transplantation period. Methods. Measurements were carried out on 25 patients with chronic end-stage renal failure qualified for allogenic renal transplantation, including 5 females and 20 males aged 20-67 (mean 43.3 years old). For determination of renal function glomerular filtration rate value has been determine using Cocroft-Gault and widely use Modification of Diet (MDRD) equation. Results. Patients after allogenic renal transplantation after a 26-week follow-up period reached CKD stage 2 according to NKF with the mean value of glomerular filtration rate GFR = 61.91 ml/min/1.73 m² (according to MDRD) and 73.46 ml/min (according to Cockroft-Gault). Conclusion. The successful kidney transplantation is not corresponding with normal renal function achievement. The estimated GFR obtained with the Cockcroft-Gault equation was consistently higher than that from the MDRD equationin patients with after renal transplantation.